Second‐Order Devolution or Local Activism? Local Air Agencies Revisited. Issue 6 (15th November 2019) - Fowler, Luke; Jones, Bryant
Abstract: In response to calls from previous scholarship for further bottom‐up examination of local government roles in environmental policy, the authors revisit local air agencies to examine two separate phenomena occurring in environmental federalism: one from the top down (second‐order devolution) and one from the bottom up (local activism). Using survey data from local air agencies on devolved authorities to set air quality standards and to enforce federal and/or state standards, the authors identify three different types of local agencies: state administrative subunits (only enforcement authority), fully devolved agencies (authority to both set and enforce standards), and activist agencies (neither authority). Further findings indicate that state administrative subunits and fully devolved agencies are likely functions of second‐order devolution, while activist agencies are likely functions of local activism. Conclusions suggest that both top‐down and bottom‐up approaches to environmental federalism are shaping local government roles in environmental management. Abstract : 二阶权力下放还是地方行动主义？重审地方航空机构: 以往学术研究呼吁对地方政府在环境政策中的作用进行进一步的自下而上式检验，为此作者重审了地方航空机构，验证发生在环境联邦制中的两种独立现象：一种是自上而下式（二阶权力下放），另一种是自下而上式（地方行动主义）。通过使用由地方航空机构提供的，关于设立航空质量标准、实施联邦和/或国家标准的分权机构数据，作者识别出三种不同类型的地方机构类型：国家行政子机构（仅执法机构）、权力全面下放机构（机构能设立并执行标准）、活动人士机构（非权威机构）。进一步研究发现显示，国家行政子机构和权力全面下放机构是二阶权力下放后可能出现的职能，而活动人士机构则可能是地方行动主义的体现。结论暗示，环境联邦制的自上而下和自下而上式措施，都在同时影响地方政府在环境管理中的作用。 Abstract : ¿Devolución de segundo orden o activismo local? Agencias aéreas locales revisitadas: En respuesta a las solicitudes de estudios previos para un examen más detallado de los roles del gobierno local en la política ambiental, los autores revisan las agencias aéreas locales para examinar dos fenómenos separados que ocurren en el federalismo ambiental: uno de arriba hacia abajo (devolución de segundo orden) y uno de abajo hacia arriba (activismo local). Utilizando datos de encuestas de agencias aéreas locales sobre autoridades delegadas para establecer estándares de calidad del aire y hacer cumplir las normas federales y / o estatales, los autores identifican tres tipos diferentes de agencias locales: subunidades administrativas estatales (solo autoridad de aplicación), agencias totalmente delegadas (autoridad para establecer y hacer cumplir estándares), y agencias activistas (ninguna autoridad). Otros hallazgos indican que las subunidades administrativas estatales y las agencias totalmente delegadas son probablemente funciones de devolución de segundo orden, mientras que las agencias activistas son probablemente funciones del activismo local. Las conclusiones sugieren que tanto los enfoques de arriba hacia abajo como de abajo hacia arriba para el federalismo ambiental están configurando los roles de los gobiernos locales en la gestión ambiental.